DEVELOPING ENGLISH WRITING MATERIALS OF DESCRIPTIVE TEXT BASED ON SCIENTIFIC APPROACH FOR GRADE X MULTIMEDIA STUDENTS AT SMKN 1 DOLOK MASIHUL - Siti Laila Barkah; Isli Iriani Indiah Pane (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
The aim of this study was to develop writing materials of descriptive text assupporting learning for grade X multimedia students at SMKN 1 Dolok Masihul. Theresearch was conducted by using Research and Development which is adapted fromBorg, Gall and Gall (2003). The data was taken from the observation, questionnaires,and interview. The materials were validated by an English lecture and an Englishteacher by using validation sheets which is adapted from BSNP. The data werecollected by using descriptive analysis. The result of this study shows that: (1) theexisting materials do not support the students study program because the topics of thematerials are still general, (2) relevant writing materials are needed by students invocational school especially in multimedia study program. The materials are designedby using Scientific Approach, (3) the developed writing materials by using ScientificApproach has been validated with the score 3.60 from the first expert and 3.53 fromthe second expert which is in the range of 3.50 < ̅≤ 4.00. The writing descriptivetext materials have been developed in accordance to the students’ need by usingScientific Approach.